Multicystic dedifferentiated retroperitoneal liposarcoma: tumour cyst fluid analysis and implications for management. (8th July 2015) - Khoury, Mitri; Sim, Geok Choo; Harao, Michiko; Radvanyi, Laszlo; Amini, Behrang; Benjamin, Robert S; Pisters, Peter W T; Pollock, Raphael E; Tseng, William W
Abstract : Liposarcomas are soft tissue sarcomas of adipocyte origin. We describe a case of a dedifferentiated retroperitoneal liposarcoma with an unusual presentation on recurrence as a large, multicystic tumour. The patient was a 72-year-old woman who had undergone multiple treatments including two prior resections. For her most recent locoregional disease recurrence, the patient was offered surgical debulking for symptom palliation. At this operation, performed after two cycles of chemotherapy, the tumour cyst fluid was analysed and found to have a predominance of immune cells with no identifiable malignant cells. This case and the results of our tumour cyst fluid analysis raise several interesting considerations for the management of this unique situation in a rare disease.